Analisis Penerapan Inovasi Digital pada Pariwisata Berkelanjutan di Kabupaten Semarang - Darmadji, Reza; Eka Fitria, Sisca (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Semarang Regency is one of Central Java's leading tourist destinations with the attraction of Gedong Songo Temple and Rawa Pening. In addition, Semarang Regency also has other tourism wealth in the form of 51 interesting tourist attractions and 55 tourist villages that are always active and continuously developed. Sustainable digital innovation helps to apply the latest digital technology to achieve creative solutions that will address long-term social, economic, and environmental problems. This study aims to determine the urgency and application of digital innovation in sustainable tourism in Semarang Regency. Using a descriptive qualitative method, data were collected through triangulation techniques including interviews, observation, and documentation. Data validity was tested through credibility, transferability, dependability, and confirmability. The data obtained were analyzed using qualitative methods starting from the pre-field stage, while in the field, until after the field activities were completed. The results show that the main implementation of Digital Innovation in Semarang Regency is the implementation of APIKS by the Tourism Office. However, there are challenges regarding technology adoption by local communities and the need for ongoing training, which require further attention from various relevant parties. This research is expected to provide an overview and serve as an evaluation of the importance of digital innovation in sustainable tourism management and suggests that local governments offer greater support in the form of policies and training programs to improve community digital skills. Future research can further explore the long-term impact of digital innovation on the social and environmental aspects of tourism.